Linguistics Spanish documentary in Brazil: dialogues between Garcia Gutierrez and Lara - Almeida, Carlos Candido de [UNESP]; Quirino da Silva Farias, Mona Cleide; Matias, Ilana Lopes (Univ Federal Santa Catarina, 2020)
Objective: To analyze the contributions of documentary linguistics through Garcia Gutierrez for the studies of documentary linguistics developed in Brazil. It intends to identify the approximations between the Spanish and the Brazilian context, highlighting the possible subsidies of the perspectives drawn in the scope of the Brazilian Information Science. Methods: It is guided by the survey of bibliographic production in national and Brazilian databases (Enancib and Brapci) and international databases (ISKO Spain I Porto and Dialnet) in order to identify the authors of documentary linguistics. On the Spanish side, he emphasizes the contributions of Garcia Gutierrez and, on the Brazilian side, the proposal that has been developed by Lara, among the authors who manifest the Brazilian view of this disciplinary attempt. Results: The documentation, in the Spanish scope or the Brazilian Information Science, has the function of systematizing the information of a certain area of knowledge. Documentary problems approach linguistics with the intention of constituting a documentary theory, however with the autonomy of its object of investigation. Documentary linguistics is presented as a discipline formed from the documentation dialogue with linguistics. Conclusions: We note an inclination for some perspectives from the French and English sides, although we consider that the few Brazilian researchers strive to make use of theories and concepts according to their realities in order to overcome them. The fact is that the term used to analyze documentary processes is documentary analysis, terminology that proves the lack of studies of documentary linguistics in the Brazilian Information Science.
Keywords: Documentation; Linguistics; Documentary Linguistics; Brazilian Information Science